Analysis of the approaches of senior management teams towards adoption of next generation library management systems: case study of Cape Library Consortium Institutions - Mfengu, Andiswa Yolanda (Library and Information Studies Centre (LISC), 2015)
Sophistication of technology has resulted in libraries having to manage print, digital and electronic resources. Managing all resource types and formats with traditional integrated library systems is ineffective as the systems were designed for physical resources. Next generation library management systems are expected to change this by integrating all library resources and providing access through a single platform, reducing the number of transaction the user has to perform. Additionally libraries will save large proportions of their budgets on hardware and software, as the systems are accessed through a web browser this will be an added benefit for libraries as the cost of acquiring electronic resources is continuously increasing. Next generation library management systems are not yet implemented in academic libraries in the Western Cape Province. To investigate the reasons for this, the author employed a qualitative case study approach in which a minimum of two members of the Executive Management of each of the four Cape Library Consortium institutions were interviewed. Data collected was analysed using NVivo analysis software, responses being analysed within the institution and compared across the other institutions.